(untitled) (Journal of Economic Research & Business Administration, 2016)
Today developments of a human resource is directly the influencing major factor on the stable economic growth of the country. The human capital in the country is based on such indicators as quality of a standard of living of the person, health, education, culture, the sociological relations. The Republic of Kazakhstan seeks to form the economy based on an innovation as the world economy developed due to realization of progressive ideas and inventions. The condition of global competitiveness puts new requirements before the countries of the world. Effective uses of the human capital and improvement of its quality the crucial role in achievement of good results of strategic programs in the country behind quality of the human capital is carried out with introduction of innovative methods in management, with use in practice of modern instruments of management and in this regard.